2022
DOI: 10.3390/encyclopedia2010018
|View full text |Cite
|
Sign up to set email alerts
|

Entropy

Abstract: The concept of entropy constitutes, together with energy, a cornerstone of contemporary physics and related areas. It was originally introduced by Clausius in 1865 along abstract lines focusing on thermodynamical irreversibility of macroscopic physical processes. In the next decade, Boltzmann made the genius connection—further developed by Gibbs—of the entropy with the microscopic world, which led to the formulation of a new and impressively successful physical theory, thereafter named statistical mechanics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 120 publications
0
26
0
Order By: Relevance
“…denotes the mean value. Equation (3) satisfies in fact the most general form for a "trace-form" entropic functional, S Ψ ({p i }) = k ∑ i p i ln Ψ (1/p i ), ln Ψ (z) being a generic monotonically increasing function which satisfies ln Ψ (1) = 0; for details, see [50,53].…”
Section: Nonadditive Entropy S Q : Where It Comes Frommentioning
confidence: 99%
See 2 more Smart Citations
“…denotes the mean value. Equation (3) satisfies in fact the most general form for a "trace-form" entropic functional, S Ψ ({p i }) = k ∑ i p i ln Ψ (1/p i ), ln Ψ (z) being a generic monotonically increasing function which satisfies ln Ψ (1) = 0; for details, see [50,53].…”
Section: Nonadditive Entropy S Q : Where It Comes Frommentioning
confidence: 99%
“…F(x, y; {η}) is assumed to be a smooth function of (x, y), which depends on a (typically small) set of universal indices {η}, defined in such a way that F(x, y; {0}) = x + y (additivity), which corresponds to the Boltzmann-Gibbs entropy. Furthermore, F(x, y; {η}) is assumed to satisfy F(x, 0; {η}) = x (null-composability), F(x, y; {η}) = F(y, x; {η}) (symmetry), F(x, F(y, z; {η}); {η}) = F(F(x, y; {η}), z; {η}) (associativity); for details and thermodynamical motivation, see [50,53].…”
Section: Nonadditive Entropy S Q : Where It Comes Frommentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015 a numerical study showed [17], for the d = 1 first-neighbor planar-rotator model, the dependence on T of σ and κ for sizes L in the range [50, 1600] and a power-law was found at high temperatures. It was shown [16] two years later that all the available results can be collapsed, for L in the range [25,2000] through the following q-Gaussian:…”
Section: High Temperature Low Temperature Flux Direction Imentioning
confidence: 99%
“…where, for d = 1, σ 0 ≡ σ (0, L) independs from L, and (q, B q ) (1.55, 0.40), the q-exponential function being defined as e z q ≡ [1 + (1 − q)z] 1/(1−q) (e z 1 = e z ). This function extremizes, under appropriate simple constraints, the nonadditive entropy [23,24,25]…”
Section: High Temperature Low Temperature Flux Direction Imentioning
confidence: 99%